Penerapan Metode System Usability Scale (SUS) dalam Menganalisis Kepuasan Karyawan Terhadap Penggunaan Aplikasi PASSION pada PT Pegadaian - Andini, Nadira; Pakpahan, Elsi Yulianti; Mesran, Mesran; Ginting, Guidio Leonarde (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
PT Pegadaian Persero is one of the State-Owned Enterprises that helps the government to provide financial solutions to customers who are experiencing financial difficulties by providing macro-scale loans or providing legal credit to customers. PT Pegadaian creates software that makes it easier for employees and clients to process all types of business processes and transactions because the company has been impacted by advances in information technology. With the increase and development of information technology, PT Pegadaian realizes that the use of information technology is very helpful in the process of optimizing business growth. The software owned by PT Pegadaian is PASSION (Pegadaian Application Support System Integrated Online). The PASSION application is an information system used in productivity and daily operations at Pegadaian, so it is necessary to pay attention to the usability level of the application so that it can make it easier for employees to apply the application. The aim of this research is to measure employee satisfaction, effectiveness and usability scores with the PASSION application used. To analyze the effectiveness, level of satisfaction and usability of the PASSION application, the System Usability Scale (SUS) method is the appropriate solution and method for evaluating system usability based on industry standards. The System Usability Scale (SUS) method was chosen because respondents can complete questions quickly and easily by filling out a questionnaire consisting of ten statements and the results are a single score from 0 to 100, which makes it relatively easy for users to understand. Based on the calculation process that has been carried out using the System Usability Scale (SUS) method, a value of 69.125 is obtained, which is in the grade C or